Pemberdayaan Bahasa Inggris SMP Swasta PKMI Efesus Aekbatu Melalui Lagu - Fiber Yun Almanda Ginting; Dyan Wulan Sari HS; Liana , Liana; Immanuel D. B. Silitonga (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2022)
When learning English, especially vocabulary for young learners, it's a good idea to use media that can capture children's attention. However, using media is not always possible or realistic for a teacher in the classroom because the use of media depends on the learning material to be conveyed to students. In teaching vocabulary, songs can be used as a good way to introduce new vocabulary to students, so that they can understand words or lessons easily and clearly. Songs that can contain information, such as words or numbers, either in one stanza or the entire song and are used in class or private study. Before this lesson, the vocabulary of students, especially about human body parts and also the names of animals in English is very limited. After this lesson, the vocabulary of students will increase, especially the vocabulary of human body parts and also the names of animals in English. It is proven that the additional learning obtained through community service activities carried out by the author can improve students' English skills, especially students' English vocabulary.